Critical analysis of sewage sludge-based organomineral fertilizers through a bibliometric perspective - Rodrigues, Mayra Maniero; Viana, Douglas Gomes; Mendonça, Rafael Santana; Capra, Gian Franco; Oliveira, Fernando Carvalho; da Silva, Luis Fernando Vieira; Nogueira, Thiago Assis Rodrigues [UNESP]; Regitano, Jussara Borges (Springer Nature, 2025)
Sewage sludge (SS), a by-product of wastewater treatment, contains organic carbon and nutrients, making it suitable for agricultural use. However, environmental concerns regarding potentially toxic elements (PTEs) and pathogens limit its direct application. The synthesis of organomineral fertilizers using SS (SS-OMFs) offers: i) safer reuse strategy, as contaminants are diluted during manufacturing; ii) socio-economic benefits, transitioning from a linear to a circular economy model; and iii) environmental sustainability, by avoiding unproductive and unsustainable landfill disposal. However, research on SS-OMFs remains limited. This critical bibliometric review, using VOSviewer and data from the Web of Science (2000–2024), reveals a growing global interest in SS-OMFs, with Brazil, Poland, and Italy leading research efforts. The analysis identifies key research hotspots, including soil fertility, nutrient recycling, and PTEs mitigation, while highlighting gaps in long-term field studies and economic feasibility. Despite progress, long-term field studies are needed to confirm their slow release of nutrients and agronomic efficacy, residual environmental impacts, and economic feasibility to drive public and private investments. This paper synthesizes existing research, identifies critical knowledge gaps, and proposes future research directions, emphasizing the need for interdisciplinary approaches combining soil science, environmental economics, and waste management to optimize SS-OMFs for sustainable agriculture.